First report of the weed Solenostemon monostachyus (P. Beauv.) Briq. (Fam. Lamiaceae) in agroecosystems in Costa Rica. - Brenes-Prendas, Steven (2013)
From 2008 to 2013, an unidentified weed was found in several fields of pineapple, bananas and ornamental plantations, in the Atlantic Region of Costa Rica. The species was determined to be Solenostemon monostachyus (P. Beauv.) Briq., an African aromatic plant. The main taxonomic characteristics for the identification of this species are included in this first report.